Rebuilding Imagination through Nostalgia: Recycling and Intertextuality in Disney Live-Action Films - Indra, Daswandi Budi (Jurnal Spektrum Komunikasi, 2025)
This article explores the concepts of intertextuality and the process of story recycling in Disney live-action films, including Maleficent (2014), The Jungle Book (2016), Beauty and the Beast (2017), The Lion King (2019), and Aladdin (2019). It highlights how Disney integrates elements from classic stories to create new narratives that resonate with modern audiences. Through a narrative analysis approach, this study examines Disney’s efforts to reconstruct collective imagination through nostalgia, manifested in intertextuality and recycling within visual elements and story development. The findings demonstrate how these strategies effectively preserve the appeal of classic tales while offering a fresh experience for contemporary viewers.